IMPLEMENTATION OF CHEMISTRY LEARNING INNOVATION INTEGRATED WITH GENERIC SCIENCE SKILLS TO ENHANCE HOTS ABILITY - Sutiani, Ani; Muchtar, Zainuddin; Dibyantini, Ratu Evina; Sinaga, Marudut; Panggabean, Freddy Tua Musa (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The integration of 21st-century learning and generic science skills (GSS) is critical in developing students' higher-order thinking skills (HOTS), especially in chemistry education. This quasi-experimental study aimed to analyze the effects of implementing four GSS-integrated digital learning models (PjBL-GSS, PBL-GSS, IBL-GSS, and DL-GSS) and students’ initial abilities on their HOTS performance. A total of 397 students participated, grouped by initial ability levels and assigned to different learning models. Data were collected using validated instruments including scholastic tests and HOTS assessments, and analyzed using descriptive statistics and two-way ANOVA. The results showed significant effects of both initial abilities and learning models on HOTS, with IBL-GSS being the most effective, especially for high-ability students. Moreover, significant interactions were found between initial ability and the type of model used. The study suggests that selecting appropriate digital learning models based on students' prior knowledge is essential to foster optimal HOTS outcomes. Teachers are encouraged to align instructional design with both GSS indicators and students’ learning readiness.